A questionnaire survey on a feeling of loneliness of the mothers raising children. Issue 12 (23rd September 2021) - Yagi, Asami; Ueda, Yutaka; Taniguchi, Mariko; Ikeda, Sayaka; Matsuzaki, Satoko; Takiuchi, Tsuyoshi; Arahori, Hitomi; Miyoshi, Ai; Hirai, Kei; Kimura, Tadashi
Abstract: Aim: A feeling of isolation childcare mothers' face is a serious social problem in Japan because the relationships with mothers and local communities have grown sparser. The purpose of this study was to clarify the feelings of isolation of mothers during childcare and the factors related to it. Methods: We conducted a questionnaire survey in Yao City, Osaka. We mailed out a questionnaire survey of 1293 mothers with infants who had either a 4‐month or 42‐month routine health checkup during the period from September to December of 2018. Results: There was no association between "feeling lonely while raising my child" and the absence of "people who helped raise my children." On the other hand, it was found that the mothers' inner feelings, such as "I wasn't satisfied with my childcare environment" (OR: 2.55, 95% CI: 1.32–4.91, p  = 0.0052) or "I lacked confidence in my own childcare abilities" (OR: 6.21, 95% CI: 4.31–8.95, p  < 0.0001), were associated with their sense of loneliness. Conclusions: Mothers' "sense of loneliness" was shown to be best correlated with their dissatisfaction with the environment of their childcare and with their lack of confidence in raising their own children.